2014
DOI: 10.1371/journal.pone.0115197
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function in Hepatosplenic Schistosomiasis – An Assessment of Renal Tubular Disorders

Abstract: BackgroundRenal involvement in Schistosoma mansoni infection is not well studied. The aim of this study is to investigate the occurrence of renal abnormalities in patients with hepatosplenic schistosomiasis (HSS), especially renal tubular disorders.MethodsThis is a cross-sectional study with 20 consecutive patients with HSS followed in a medical center in Maceió, Alagoas, Brazil. Urinary acidification and concentration tests were performed using calcium chloride (CaCl2) after a 12-h period of water and food de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
1
15
1
5
Order By: Relevance
“…In this study, we observed higher levels of urinary MCP‐1 (uMCP‐1) that were correlated with an increase in albuminuria, even after testing inflammatory interference. Our previous studies with other infectious disease, including VL, hepatosplenic schistosomiasis and leprosy (mostly as the lepromatous form) showed patients also had these clinical complications, including urinary oxidative stress, suggesting an increased risk of kidney disease development in these patients . Despite the important involvement of uMCP‐1 in renal interstitium inflammation and glomerulonephritis in VL, the present study showed it was not related with AKI development in the univariate analysis and that it had a poor diagnostic performance in the ROC curve analysis.…”
Section: Discussioncontrasting
confidence: 70%
“…In this study, we observed higher levels of urinary MCP‐1 (uMCP‐1) that were correlated with an increase in albuminuria, even after testing inflammatory interference. Our previous studies with other infectious disease, including VL, hepatosplenic schistosomiasis and leprosy (mostly as the lepromatous form) showed patients also had these clinical complications, including urinary oxidative stress, suggesting an increased risk of kidney disease development in these patients . Despite the important involvement of uMCP‐1 in renal interstitium inflammation and glomerulonephritis in VL, the present study showed it was not related with AKI development in the univariate analysis and that it had a poor diagnostic performance in the ROC curve analysis.…”
Section: Discussioncontrasting
confidence: 70%
“…The Sm PCR + group is characterized by the absence of eggs but the presence of worms. schistosome-related nephropathy and renal damage [29,30]. However, within our study cohort, CCL2 was the only chemokine that was not altered between the analysed groups, did not correlate with egg burden nor was it associated with any of the included groups within the regression analyses.…”
Section: Discussionmentioning
confidence: 58%
“…In terms of pathology, CCL3 [27] and CCL5 [28] were shown to be decreased in cases of periportal fibrosis, although de Souza and colleagues did not confirm the CCL5 data from Booth et al . schistosome-related nephropathy and renal damage [29,30]. 4.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of 20 HSS patients in our group, acidification deficit and urinary concentration inability were observed in 45% and 85% of the patients, respectively. Moreover, urinary MCP-1 (monocyte chemotactic protein-1) values were higher in the HSS group than healthy control group and were positively correlated with 24-hour albuminuria and proteinuria levels [6].…”
Section: Introductionmentioning
confidence: 92%